Reversible facial nerve paralysis in a cat suspected to be associated with systemic hypertension. Issue 2 (December 2021) - Moretto, Laura; Herzig, Robert; Beckmann, Katrin; Wolfer, Nadja; Dennler, Matthias; Glaus, Tony M
Case summary: This report describes the appearance of facial nerve paralysis in a 16-year-old hypertensive cat. MRI was helpful in visualising and characterising mesencephalic and facial nerve lesions thought to be induced by hypertension. Neurological signs rapidly resolved under antihypertensive therapy. Relevance and novel information: Systemic hypertension is an important medical condition in geriatric cats causing damage in various target organs, including the brain. Hypertensive encephalopathy is an umbrella term for a multitude of different clinical manifestations of cerebral target organ damage. Facial nerve paralysis secondary to hypertension is recognised in human medicine, particularly in children, but so far has not been reported in veterinary medicine.